Orientational Coupling Locally Orchestrates a Cell Migration Pattern for Re-Epithelialization - Hu, Benhui (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.